ANALISIS TINDAK TUTUR PADA FILM IMPERFECT: KARIR, CINTA DAN TIMBANGAN KARYA MEIRA ANASTASIA : KAJIAN PRAGMATIK - Via Renita Lubis; Marlina Agkris Tambunan; Vita Riahni Saragih; Jumaria Sirait; Immanuel Doclas Belmondo Silitonga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe locutionary, illocutionary, and perlocutionary speech acts in the film Imperfect: Career, Love, and Scales by Meira Anastasia through pragmatic studies. The study uses a qualitative descriptive method with data sources in the form of dialogue in the film. Data collection is carried out through listening, note-taking, and documentation techniques, while data analysis uses an interactive analysis model. The results of the study show that locutionary speech acts are used to convey information directly, illocutionary speech acts are used to convey certain intentions such as giving advice, requesting, insinuating, motivating, and expressing attitudes, while perlocutionary speech acts show the impact of speech on the interlocutor in the form of changes in attitude, emotion, or action. These three types of speech acts are interrelated in forming contextual and functional communication in social interactions in the film.